From barefoot hunter gathering to shod pavement pounding. Where to from here? A narrative review. Issue 1 (21st April 2020) - Francis, Peter; Schofield, Grant
Abstract : Understanding the current prevalence and incidence of running injury from an evolutionary perspective has sparked great debate. Proponents of the evolutionary approach to understanding running injury suggest that humans ran using less injurious biomechanics prior to the invention of cushioned running shoes. Those who disagree with this view, point to the many runners, wearing cushioned running shoes, who do not get injured and suggest that the evolutionary approach is indulging in a 'natural fallacy'. This polarises the scientific debate into discrete categories such as 'shod' vs 'barefoot'. This review aims, first, to describe humans' innate impact moderating mechanisms which arise from our evolutionary legacy. Second, we discuss the impact of footwear on these mechanisms and the potential link to injury in some runners. Finally, we discuss the role of barefoot training in sports medicine and attempt to make some practical suggestions as to how it might be integrated in our modern urban environments.